Development of Moodle-Based Learning Management System Integrated with Virtual Programming Lab for Basic Vocational Subjects of Software and Game Development - Akbar Muzaki; Abna Hidayati; Ulfia Rahmi; Ridwan (Postgraduate, University of Mataram, 2025)
Programming instruction in Vocational Basics for Software and Game Development (PPLG) often encounters challenges such as limited lab practice time, restricted learning media, and conventional one-way teaching methods. This study aims to develop a Moodle-based Learning Management System (LMS) integrated with a Virtual Programming Lab (VPL) that is valid, practical, and effective. Utilizing the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), the LMS was tested on 36 grade X PPLG students at SMKN 2 Padang. Results showed high validity with a score of 4.4 (highly feasible), practicality scores of 5.0 (teachers) and 4.4 (students) (highly practical), and effectiveness with an N-gain of 0.80 (high). The findings indicate that the LMS significantly enhances learning outcomes, offering a flexible and effective solution for teaching Vocational Basics. This study concludes that the Moodle-based LMS with VPL integration is a viable tool to address existing instructional challenges in PPLG education.